The European Court of Human Rights Overwhelmed by Applications: Problems and Possible Solutions - Deutsch, Ulrike.; Wolfrum, R<U+00fc>diger. (Beitrg̃e zum auslñdischen f̲fentlichen Recht und Vl̲kerrecht, Verf̲fentlichungen des Max-Planck-Instituts f<U+00fc>r auslñdisches f̲fentliches Recht und Vl̲kerrecht,, 2009)
The European Court of Human Rights is faced with an enormous and ever-increasing caseload, which poses a considerable threat to the effectiveness of the protection of the rights guaranteed by the European Convention on Human Rights and its Protocols. Compiling the contributions of distinguished academics and practitioners who are active in the field of European human rights law, this publication is meant as a contribution to the still ongoing discussion on the reform of the control mechanism of the European Court of Human Rights, which is necessary to prevent a failure of the European system of human rights protection.